PERILAKU MENYIMPANG YANG “SERING” DILAKUKAN OLEH SISWA KELAS TINGGI SDN 15 JOLLE TAHUN AJARAN 2022/2023 - Sudarto Sudarto; Muhammad Idris Jafar; Mifta Madaniah (Bajang Institute, 2023)
The background of this research was that there were several elementary school-age students at SDN 15 Jolle, Lalabata District, Soppeng Regency, who “ofte”n engage in deviant behavior. This research is a survey research that aimed to find out the forms of deviant behavior that were